Proceedings of the International Joint Conference on Work Activities Coordination and Collaboration 1999
DOI: 10.1145/295665.295667
|View full text |Cite
|
Sign up to set email alerts
|

A reference model for workflow application development processes

Abstract: The success of workflow projects to a large extent depends on how workflow application development processes are planned, organized, and conducted. Based on lessons learned from problems encountered during real-world workflow application development projects, this paper presents a reference model for workflow application development processes, which guides project managers and developers through the complex structure of these processes, with the aim of developing more adequate, usable, and reliable workflow ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Many researchers studied the business process model from a variety of directions; the compendium of this work provides a complete picture of the enterprise's procedures [32] [33] [63]. Other prominent approaches to business process modeling procedures are presented in [64] [65], which address the procedures to gather the requirements to build a model. Several ideas regarding the acquisition of requirements to develop a business process are mentioned in the articles [66] [67].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers studied the business process model from a variety of directions; the compendium of this work provides a complete picture of the enterprise's procedures [32] [33] [63]. Other prominent approaches to business process modeling procedures are presented in [64] [65], which address the procedures to gather the requirements to build a model. Several ideas regarding the acquisition of requirements to develop a business process are mentioned in the articles [66] [67].…”
Section: Related Workmentioning
confidence: 99%
“…Several ideas regarding the acquisition of requirements to develop a business process are mentioned in the articles [66] [67]. In addition, several articles have stated that requirements engineering is appropriate to build the business process models; refer to [64] [65].…”
Section: Related Workmentioning
confidence: 99%
“…Workflow [8][9][10][11][12][13][14][15][16] has been used (WfMC), workflow focuses on handing business processes. It is concerned with the automation of procedures where information and tasks are passed between participants according to a defined set of rules to achieve, or contribute to, an overall business goal.…”
Section: Workflow Technologymentioning
confidence: 99%
“…We assume that the business processes examined in the analysis phase have been derived by process analysts, possibly by using the methods proposed in the literature (based on interviews, surveys, team discussions, and so on -see [20] for a discussion). Since an automatic transfer of business process models into workflow models proves impractical [20], an intermediate phase is needed for analysing the organisational structure and the existing technical structure of the company, i.e., existing (legacy) systems and system distribution issues. During workflow analysis, requirements are refined and structured, using the language of the developers and treating issues regarding the system activities and roles, the anomalous cases, the distribution and cooperation requirements, and the relationships with other systems.…”
Section: Workflow Analysismentioning
confidence: 99%
“…Indeed, it has been shown that an early and inappropriate WfMS selection may lead to considerable difficulties in the implementation and enactment of the workflow processes [20].…”
Section: Selection Of the Target Workflow Management Systemmentioning
confidence: 99%